Archival Description, Land, Settler Colonialism, and World-Building in the Collection des archives du Collège Sainte-Marie - Aton, Henria; Dansereau, François; Nugent, Kate (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie, 2024)
When the Society of Jesus returned to Turtle Island in the 1840s after the suppression of their order in 1773, searching for and consolidating the records they had been forced to leave behind was of utmost importance. The first Jesuit archivists set out to copy legal documents from Jesuits in Europe, records of their travels, and of correspondence between Jesuits in France, to build a coherent narrative of their order that foregrounded a sense of continuity with their forebears. The consolidation of these records led to the creation of the Collection des archives du Collège Sainte-Marie (CACSM). This article puts forward a case study that explores the description of records in the CACSM catalogue and the persistence and normalization of the catalogue descriptions into its later forms such as the index and internal database. It builds on recent scholarly examination of cataloguing systems and archival descriptions that have defined these as systems of knowledge, infrastructures of power, and tools of colonialism. We begin by arguing that the descriptive indicators of both original records and copies emphasized land as a means to assert Jesuit presence and influence, revealing the profound connection between the archive and settler colonialism. Then, we show that these descriptions were crucial actors that mobilized knowledge production by naming, framing or erasing information to meet the settler-colonial worldview. Finally, we demonstrate that the persistence of these catalogue descriptions, through the creation of other indexes and finding aids in the 1950s and beyond, signify their structural impact and functions.